Probiotic fermentation improves the bioactivities and bioaccessibility of polyphenols in Dendrobium officinale under in vitro simulated gastrointestinal digestion and fecal fermentation - Li, Rurui; Wang, Zhenxing; Kong, Kin Weng; Xiang, Ping; He, Xiahong; Zhang, Xuechun (Frontiers in Nutrition, 2022)
The objective of the research was to investigate and compare the bioactivities and bioaccessibility of the polyphenols (PPs) from Dendrobium officinale (DO) and probiotic fermented Dendrobium officinale (FDO), by using in vitro simulated digestion model under oral, gastric and intestinal phases as well as colonic fermentation. The results indicated that FDO possessed significantly higher total phenolic contents (TPC) and total flavonoid contents (TFC) than DO, and they were released most in the intestinal digestion phase with 6.96 ± 0.99 mg GAE/g DE and 10.70 ± 1.31 mg RE/g DE, respectively. Using high-performance liquid chromatography (HPLC), a total of six phenolic acids and four flavonoids were detected. In the intestinal phase, syringaldehyde and ferulic acid were major released by DO, whereas they were p-hydroxybenzoic acid, vanillic acid, and syringic acid for FDO. However, apigenin and scutellarin were sustained throughout the digestion whether DO or FDO. As the digestive process progressed, their antioxidant ability, α-amylase and α-glucosidase inhibitory activities were increased, and FDO was overall substantially stronger in these activities than that of DO. Both DO and FDO could reduce pH values in the colonic fermentation system, and enhance the contents of short-chain fatty acids, but there were no significantly different between them. The results of the 16S rRNA gene sequence analysis showed that both DO and FDO could alter intestinal microbial diversity during in vitro colonic fermentation. In particular, after colonic fermentation for 24 h, FDO could significantly improve the ratio of Firmicutes to Bacteroidetes, and enrich the abundancy of Enterococcus and Bifidobacterium (p < 0.05), which was most likely through the carbohydrate metabolism signal pathway. Taken together, the PPs from DO and FDO had good potential for antioxidant and modulation of gut bacterial flora during the digestive processes, and FDO had better bioactivities and bioaccessibility. This study could provide scientific data and novel insights for Dendrobium officinale to be developed as functional foods.